EFFECT OF A SUBSURFACE PLASTIC FILM INSERTION SYSTEM ON SOIL MOISTURE REGIME - Abs, José; Ferreira Gomes, Marco Antônio; Ferreira Filizola, Heloísa; Salemi, Luiz Felippe (REVISTA DE AGRICULTURA, 2025)
Systems that enhance water retention in soils have the potential to increase agricultural production and mitigate the effects of droughts. In the present study, the effect of a Subsurface Plastic Film Insertion System (SPFIS) on soil water retention was evaluated. Four plots were established using the plastic film, applied through subsoiling at a depth of 40 cm. Tensiometers were installed at soil depths of 0-10 cm, 10-20 cm, 20-30 cm, and 30-40 cm, and tension was recorded weekly. The results indicated lower soil water matric potential values in the plots with the plastic film compared to the control plots (without the film). These result can be attributed to the increased water retention and concentration around the films, which also resulted in a longer duration of elevated soil moisture content, even during periods of no rainfall. The SPFIS contributed to increased soil moisture, with the potential to enhance agricultural productivity.